LncRNA‐XIST/microRNA‐126 sponge mediates cell proliferation and glucose metabolism through the IRS1/PI3K/Akt pathway in glioma. Issue 3 (3rd November 2019) - Cheng, Zhihua; Luo, Cong; Guo, Zhilin
Abstract: Abnormal glucose metabolism may contribute to cancer progression. Glioma represents a cancer resulting from an imbalance between glucose metabolism and tumor growth. However, the molecular mechanisms responsible for dysregulated brain glucose metabolism and lactate accumulation in glioma remain to be elucidated. The present study identified a long noncoding RNA (lncRNA) X‐inactive specific transcript (XIST) as a candidate to mediate glucose metabolism in glioma. Cell viability, migration, invasion, and resistance to apoptosis were evaluated in lncRNA‐XIST‐depleted glioblastoma cells by short hairpin RNA. Glucose uptake, lactate production, as well as levels of glucose transporter 1 (GLUT1) and GLUT3, were measured. Luciferase assay, RNA pull‐down, and RNA immunoprecipitation were performed to validate the interactions among lncRNA‐XIST, microRNA‐126 (miR‐126), and insulin receptor substrate 1 (IRS1). An in vivo analysis was carried out in nude mice bearing glioblastoma cell xenografts. The study found that lncRNA‐XIST knockdown inhibited cell viability, migration, invasion, resistance to apoptosis, and glucose metabolism of glioblastoma cells. LncRNA‐XIST functioned as a competing endogenous RNA of miR‐126 and then regulated IRS1/PI3K/Akt pathway in glioblastoma cells. In vivo results demonstrated lncRNA‐XIST knockdown reduces the tumorigenicity of glioblastoma cells. Taken together, we demonstrated a novel cellular mechanism that was dependent of the lncRNA‐XIST/miR‐126/IRS1/PI3K/Akt pathway in enhanced glucose metabolism in glioma. Abstract : We found that long noncoding RNA (lncRNA)‐XIST knockdown inhibits cell viability, migration, invasion, resistance to apoptosis, and glucose metabolism of glioblastoma cells. LncRNA‐XIST functions as a competing endogenous RNA (ceRNA) of microRNA‐126 (miR‐126) and then regulates the IRS1/PI3K/Akt pathway in glioblastoma cells. In vivo results were reproduced in in vivo studies, which demonstrated lncRNA‐XIST knockdown reduces the tumorigenicity of glioblastoma cells.The study provides a rationale for further analysis of lncRNAs in glioma treatment.